2017
DOI: 10.15381/rivep.v28i3.13360
|View full text |Cite
|
Sign up to set email alerts
|

Interacción Humano-Animal y Prácticas de Manejo Bovino en Subastas Colombianas

Abstract: RESUMENEl objetivo del estudio fue evaluar las interacciones humano-animal (IHA) y las prácticas de manejo en subastas de Medellín, Colombia. Se recopilaron datos de cuatro subastas ganaderas realizadas en junio de 2014. Se evaluaron 720 bovinos, los cuales, durante el pesaje y la conducción se subdividieron en 241 lotes y 28 grupos de lotes, respectivamente. Se caracterizaron los hallazgos en inspección veterinaria, así como las interacciones táctiles, auditivas y visuales de los manejadores y las respuestas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
(19 reference statements)
4
5
0
2
Order By: Relevance
“…Freezing is considered as a fear response by cattle, which makes them more skittish and difficult to handle [20]. In this study, auditory interactions generated limited responses in steers; similar results have been reported in cattle auctions [28]. In Colombia, auditory interactions such as shouting, which are considered negative by some authors [31], or neutral by others [34], did not affect the behavior in commercial Zebu young bulls, perhaps due to a process of habituation with this type of handling [22], taking into account that the use of human vocalizations and sounds is a common practice for the handling of commercial Zebu young bulls [12].…”
Section: Handling Assessmentsupporting
confidence: 82%
See 2 more Smart Citations
“…Freezing is considered as a fear response by cattle, which makes them more skittish and difficult to handle [20]. In this study, auditory interactions generated limited responses in steers; similar results have been reported in cattle auctions [28]. In Colombia, auditory interactions such as shouting, which are considered negative by some authors [31], or neutral by others [34], did not affect the behavior in commercial Zebu young bulls, perhaps due to a process of habituation with this type of handling [22], taking into account that the use of human vocalizations and sounds is a common practice for the handling of commercial Zebu young bulls [12].…”
Section: Handling Assessmentsupporting
confidence: 82%
“…In this study, handlers used visual interactions such as hand raising, waving and blocking, which are consistent and accepted for minimally invasive handling of groups of cattle [2], and which are frequently used in cattle auctions in Colombia [28]. However, the study observed significant positive correlations between blocking and the behavioral responses of steers, such as slipping and falling, probably because driving represents a novel event for cattle which generates challenges, emotions and alertness [28,30].…”
Section: Handling Assessmentmentioning
confidence: 85%
See 1 more Smart Citation
“…NTI like hitting, poking, kicking, and even tail twisting have been often observed during handling at cattle markets as it has been reported in earlier studies in the United Kingdom (4, 9); in Bangladesh (28); in Colombia (29,30) and also in Chile (8,10,11). The most common NTI in the present study were hits and pokes, whereas kicking was uncommon ( Table 3).…”
Section: Negative Tactile Interactions With Handlerssupporting
confidence: 78%
“…As regards interactions like whistling and speaking, various studies have concluded that they have a neutral effect on the cattle behavior [ 29 , 30 ]. We suggest that handling the cattle in this way can have a calming effect and alert the cattle that the handler is approaching, especially as these are common methods employed in Colombia; as has been shown in livestock abattoirs and auctions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%